The Influence of Home Industry Batik on Enhancement Village Community Income Pungsari , Plupuh , Sragen year 2021 - Rika Puji Rahayu (Universitas Veteran Bangun Nusantara, 2022)
Sragen is one districts in Central Java which have potency featured and functions in various sectors that can utilized for increase well- being and improve income society . One of them is in the field of industry . Home industry small medium that can increase income public is the home industry of batik. in the village Pungsari districts Plupuh districts Sragen have some batik home industries that can increase income public around with frequent batik called Batik Girli (Batik Pinggir Kali). Destination study this is analyze the influence of the batik home industry on enhancement income public village Pungsari districts Plupuh districts Sragen . Type study this is descriptive with approach qualitative . Data collection techniques used among others: 1). Observation informants , 2). Survey field , 3). Interview deep , 4). Documentation . Research results show that the batik home industry has influence in enhancement income public about , that is Rp. 450,000 – Rp. 600,000 each the month . Efforts made _ batik industry home owner for increase income public around is with take batik industry home worker from public around and add results batik production as well expand the market so that will add workers ' income.